How rewilding impacts ecosystem health in a semi-arid region - Faria, Alexandro Carlos (Department of Biological Sciences, 2025)
Rewilding represents more than just the reintroduction of iconic charismatic species; it holds the potential to assist in reestablishing critical ecosystem functions, helping create dynamic, resilient, and self-sustaining ecosystems. Here I test the general idea that the reintroduction of megafauna such as elephant, rhino, and buffalo will alter soil and vegetation characteristics as well as dung beetle assemblages via megafauna trampling and feeding behaviours, ultimately improving ecosystem health. This was conducted in two different vegetation types, Montagu Shale Renosterveld and Western Klein Karoo. By examining these key indicators of ecosystem health, this research has revealed that the rewilded areas generally exhibit higher levels of dung beetle abundance (up to 3.7 times higher than livestock areas), improved soil dynamics (e.g. 11–12% lower bulk density), and greater vegetation productivity as shown by EVI trends. The study also investigated the potential of leveraging carbon credits as a means to fund restoration projects in semi-arid settings, but ultimately concluded that a more nuanced approach is likely needed in the form of biodiversity credits. Ultimately, this study provides tentative evidence that well-managed rewilding can indeed assist in restoring degraded landscapes. This, in turn, reaffirms the crucial role of nature-based solutions in biodiversity conservation and highlights the importance of positive land stewardship and management. These findings underscore the importance and viability of embracing rewilding as a legitimate method by which to protect and regenerate degraded landscapes. In addition, this study illustrates how the impact of rewilding is not uniform across ecosystem types by comparing findings between the two stated vegetation types. All these findings suggest that a more holistic approach is needed to evaluate and value rewilding initiatives, one which includes key ecological variables such as vegetation dynamics, various soil characteristics, and insect populations. By taking an interdisciplinary approach to conservation through combining rigorous ecological assessments with innovative financing mechanisms (such as biodiversity credits) in the future, it is more likely to capture the multifaceted benefits of rewilding and foster long-term ecosystem resilience. This comprehensive strategy is pivotal for transforming biodiversity conservation and ensuring robust ecological recovery across diverse landscapes, while increasing the likelihood of financial viability and sustainability of rewilding projects.